Indications of enhanced soil ecosystem functions in polyculture reforested grassland - Baldos, Angelica P.; Rallos, Roland (Annals of Tropical Research, 2019)
A lot of work has been doneto evaluate the effects of biodiversity on ecological functions in polyculture plantings. But attention is rarely given to soil ecosystem functions such as carbon (C) sequestration and nitrogen (N) cycling even though they play a critical role in climate regulation through the sequestration and release of greenhouse gases (GHGs). In this study, stable isotopes of C and N were used to investigate if the aforementioned soil ecosystem functions are enhanced under polyculture reforestation by determining the sources of C stored in soil, its rate of incorporation, and the degree of soil N cycling. Twenty-five years after its establishment on an Imperata cylindrica grassland, the tree plantation has contributed 54% of the measured soil organic carbon (SOC) stock at an estimated rate of 2.41Mg C ha-1 yr-1. Larger mean soil 15N values and a more negative 15N enrichment factor (ε = -5.82‰) for the whole 50cm soil depth in tree plantation indicated a better N cycling compared to grassland vegetation. Results show the potential of polyculture reforestation as a sustainable approach to restoring degraded lands and enhancing the role of soil in climate regulation by improving the capacity of soil to store C and to supply N. In addition, information generated from studies like this allow the refinement of mechanisms used in payments for ecosystem services to add more value and provide higher incentives from the ecosystem services provided by polyculture reforestation.